Hybrid POLCA in a job shop environment - How, Whee Ching (2017)
In Malaysia, Small and Medium Enterprises (SMEs) are important engines of economic growth and development of the country. By 2020, Malaysian SMEs aim to contribute 42% to the country’s gross domestic product (GDP). However, in the present scenario, most SMEs which supply low-volume products and custom-engineered manufacturers are confronted with various challenges in retaining their competitive advantages in the global market. This study was conducted in a precision component manufacturing company that experiences low on-time delivery (OTD) of about 70%. The aim of the study was to improve the manufacturing critical-path time (MCT) and hence ensure on-time delivery to customers by adopting Quick Response Manufacturing practices and tools in the shop floor of the company. The Paired-cell Overlapping Loops of Cards with Authorization (POLCA) mechanism was employed to control material flow betwen workstations. Two modules were first built to automate the mapping of MCT for all products and to calculate the required number of POLCA cards. These informaton were then fed into a simulation model of the production floor from the company. A simulation base model was built and validated followed by experimentations ofthe original POLCA and 2 hybrid POLCA variants i.e. short processing time (SPT- POLCA) and Due Date (DD-POLCA) variants. The performance measures of these models: throughput (TP), work-in-process (WIP), average MCT per job and On-time delivery (OTD) were analysed and compared. Results showed that SPT-POLCA performed best in comparison to the other control systems. SPT-POLCA recorded the highest throughput and OTD, lowest WIP and average MCT per job. Finally, a POLCA game was developed as a teaching and training tool for engineering undergraduates and industry personnel respectively. The game provided the simplicity and hands-on experience for the players to understand the POLCA mechanism. The game was also flexible in allowing experimentations with the different POLCA variants and other manufacturing techniques.